LCA of integrated orange production in the Comunidad Valenciana (Spain). (7th June 2005) - Sanjuan, N.; Ubeda, L.; Clemente, G.; Mulet, A., F. Girona
In order to perform an LCA of integrated orange production in the Comunidad Valenciana two representative areas were studied. The functional unit was 1 kg oranges at the farm gate. Eight scenarios were considered according to type of irrigation, the origin of water and the tillage practice. The production of agrochemicals, the production and use of energy in agriculture (for irrigation and machinery), and the agricultural practices were included in the study. Hot spots were detected. Although differences were found between scenarios, it was difficult to establish which one is the best because some practices, such as tillage, are more advisable when considering herbicide production, but the herbicides used are more toxic. The lack of environmental information for agricultural LCA in Spain and the need to adapt some aspects of impact methodology to the Spanish soil and climate characteristics have also been pointed out.